2022
DOI: 10.3389/fviro.2022.972156
|View full text |Cite
|
Sign up to set email alerts
|

Predicted cellular interactors of the endogenous retrovirus-K protease enzyme

Abstract: Retroviral proteases are essential enzymes for viral replication and drive changes within the cellular proteome. While several studies have demonstrated that protease (PR) enzymes from exogenous retroviruses cleave cellular proteins and modulate cellular signaling, the impact of PRs encoded by endogenous retroviruses within the human genome has been largely overlooked. One human symbiont called Endogenous retrovirus-K (ERVK) is pathologically associated with both neurological disease and cancers. Using a compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 132 publications
(156 reference statements)
0
0
0
Order By: Relevance
“…By studying the genomes of over 300 bird species, our study unveiled the burst of ERVK throughout the diversification of Passeriformes, especially in the parvorder Passerida after Paleogene-Neogene boundary (around 22.4 MYA). Previous studies have identified ERVK-like sequences across a diverse range of organisms, including primates, rodents, ungulates, fish, and insects 40,41 . It is interesting to note that the invasion of ERVK in the genomes of some of these taxa occurred during the more recent radiation [42][43][44] , which occurred in geological periods prior to the Passeriformes radiation.…”
Section: Discussionmentioning
confidence: 99%
“…By studying the genomes of over 300 bird species, our study unveiled the burst of ERVK throughout the diversification of Passeriformes, especially in the parvorder Passerida after Paleogene-Neogene boundary (around 22.4 MYA). Previous studies have identified ERVK-like sequences across a diverse range of organisms, including primates, rodents, ungulates, fish, and insects 40,41 . It is interesting to note that the invasion of ERVK in the genomes of some of these taxa occurred during the more recent radiation [42][43][44] , which occurred in geological periods prior to the Passeriformes radiation.…”
Section: Discussionmentioning
confidence: 99%